LAPORAN KASUS CARPAL TUNNEL SYNDROME PADA DATA ANALIS - Ayesha Khayana Syarif; Elizabeth Ravinka Rossabel; Muhammad Shadam Thalib; Alvin Mohamad Ridwan (Fakultas Kedokteran Universitas Trisakti, 2024)
Background The National Health Interview Study (NHIS) estimates a 1.55% prevalence of Carpal Tunnel Syndrome (CTS) among adults, with women being more affected, especially those aged 25-64. In Indonesia, CTS prevalence is not well-documented. High-risk jobs show a CTS prevalence of 5.6% to 14.8%. Repetitive movements are a significant risk factor. This paper examines CTS in computer users. Case Description A 54-year-old male data analyst reported numbness and tingling in his right hand fingers after typing. Physical exams confirmed CTS. He works 8 hours daily, 5 days a week, without breaks or hand stretches, with no history of diabetes or trauma. Results CTS risk management includes: Engineering Controls: Voice control, ergonomic workspace adjustments. Administrative Controls: Hiring more staff, educating on hand stretches and proper wrist alignment. Personal Protective Equipment: Wrist braces. Discussion The patient has worked as a data analyst for 29 years, using a computer for 5-7 hours daily, exceeding the safe limit. Studies link prolonged computer use and CTS, with repetitive wrist movements increasing risk.